Optical properties of SiO2/TiO2 thin layers prepared by sol–gel method - Nocuń, Marek; Kwaśny, Sławomir; Zontek, Joanna (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
In this investigation, SiO2/TiO2 thin films were prepared on glass and quartz glass substrates by dip coating sol–gel technique. The films were calcinated at 500 °C for 1 hour. Thickness of the films was estimated by ellipsometric measurements and it was in the range from about 30 nm to 700 nm. Refractive index of the films was also established. Chemical composition of the samples was studied by photoelectron spectroscopy. Transmittances of the samples were characterized using UV–VIS spectrophotometer. Subsequently, band gap energy (Eg) was estimated for these films. It was found that band gap energy increases with thickness of the films and their value depends on sodium diffusing from glass substrate.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 979-987
Keywords: sol-gel; optyka; optical properties; band gap energy; SiO2–TiO2 thin films